The association between different insulin resistance indexes and bone health in the elderly - Tianjie Lai; Zhihao Su; Rui Chen; Guangan Luo; Sibo Xu; Hangqi Fang; Huanxin Yan; Peng Shen; Konghe Hu (PLoS ONE, 2025)
The triglyceride-glucose (TyG) index and its related indexes (TyG-BMI, TyG-WC, TyG-WHtR) are effective markers for screening metabolic diseases like insulin resistance (IR). However, few studies have explored the relationship between the TyG and its related indexes with bone density (BMD), osteopenia, and osteoporosis. This is a cross-sectional study that involved 1,303 adults aged 50 years and above from the National Health and Nutrition Examination Survey 2007–2010, and 2013–2014. In the multivariable-adjusted model, linear regression analysis and logistic regression analysis demonstrated that TyG and its related indexes have a significant positive correlation with BMD and a negative correlation with osteopenia/osteoporosis in the femoral neck, lumbar spine, and total hip region. Trend analysis further confirms these associations (p < 0.05). Restricted cubic spline analysis showed a nonlinear relationship between these indexes with BMD and osteopenia/osteoporosis. Sensitivity analyses further confirmed the robustness of these associations. This study reveals the significant and complex correlation between the TyG and its related indexes with BMD and osteoporosis, indicating the potential link between IR and bone health. The TyG and related indexes offer a new perspective for the diagnosis, prevention, and treatment of osteoporosis.